Déprises sexuelles : penser le vieillissement et la sexualité - Marc Bessin; Marianne Blidon (Genre, Sexualité et Société)
Sociology of aging has evolved from a functionalist analysis of disengagement to a constructionist approach examining attempts to maintain integrity of self-concept despite physical and social decline [déprise], too often forgetting sexuality. The authors call for more thought about the process of adjustment to life circumstances, starting from an analysis of attempts to maintain sexual self-concept that links together gender and life course, sex and age, taking into account relationship factors such as widowhood. The article also explores the limits and possibilities of renewal practices in old age, regardless of their sexuality. It concludes by calling for moreresearch on the subject, which is able to improve our understanding of a dynamic theme and suitable for renewed ethical reflection.